Local V4-UPM strain Newcastle virus-induced cell death of brain tumor cell lines - Ibrahim, Rohaya (2011)
V4-UPM strain is a local heat resistant variant of the avirulent Australian V4 (QUE) strain which has higher thermostabilities of infectivity and haemagglutination than the original. The aims of this study were to analyze the cytolytic effect and mode of cell death induced by V4-UPM strain of NDV on two human brain tumor cell lines, glioblastoma multiforme (DBTRG.05MG) and anaplastic astrocytoma cells (U87MG).In-vitro cytotoxic activity has been performed on both brain tumor cells via standard MTT assay. At 72 hours post-incubation, the IC50 values obtained were 30 haem agglutination (HA) unit/ml and 5 HA unit/ml for DBTRG.05MG and U87MG cells,respectively. In addition, V4-UPM strain inhibited the proliferation of both DBTRG.05MG and U87MG cells via the same method. Morphological changes of the treated cells also have been observed sequentially under the inverted light, fluorescence and electron microscopes. The virus-infected cells showed apoptotic features such as the cell shrinkage, cell blebbing and formation of apoptotic bodies under the inverted light microscope. The differential uptake of acridine orange and propidium iodide dyes demonstrated the occurrence of apoptosis, mainly by chromatin condensation and DNA fragmentation that were observed under fluorescence microscope. The next morphological observation was based on color and nuclear morphology where the nuclei of treated-cells possessed DNA fragmentation were stained dark brown by 3’,3’-diaminobenzidine. The distinct ultrastructural changes occurred in the nucleus, cellular organelles and plasma membrane structures were confirmed to be the apoptotic features via transmission electron microscopic (TEM) observation. The result of flow cytometric analyses based on annexin V-FITC that binds phosphatidylserine residue also suggested the onset of apoptosis for both groups. Meanwhile, the cell cycle was arrested at S phase followed by apoptosis. Based on these findings, it was confirmed that the V4-UPM strain induced apoptotic cell death on DBTRG.05MG and U87MG cells. Thus, this strain has the potential to be developed as an antitumor agent for future treatment particularly in grade-III brain tumor patients.